The Effect of Exhaust Manifold Diameter Variation on Engine Performance of 1300 cc Gasoline Engine - Wahyudin, Fadly Haries; Khambali, Khambali; Winoko, Yuniarto Agus (Indonesian Journal of Advanced Research, 2024)
One of the critical components responsible for channeling combustion gases from the engine to the exhaust is the exhaust manifold. Changes in the configuration and diameter of the exhaust manifold have an impact on engine performance. This study aims to understand how changes in exhaust manifold configuration and diameter affect torque and BMEP in a 1300 cc gasoline engine through an experimental approach that includes quantitative research methods. The experiment utilized 4-2-1 configuration exhaust manifolds with diameters of 32, 35, and 38 mm. Data collection of torque and BMEP was done using a dynamometer which was then processed into a graph and analyzed using anova. The highest torque value of 1300 cc gasoline engine is found on exhaust manifold with 38 mm diameter variation with torque value of 108.06 Nm, and the highest BMEP value is 1046.18 kPa. It can be concluded that the larger the diameter of the exhaust manifold, the combustion airflow coming out of the engine becomes more optimal, smoother, and there is no back pressure on the engine.